Respostas
respondido por:
1
Oi
5(1 - x) - 2x + 1 = - 3(2 + x)
aplica a distributiva
5 - 5x - 2x + 1 = - 6 - 3x
- 7x + 6 = - 6 - 3x
6 + 6 = - 3x + 7x
4x = 12
x = 12 / 4
x = 3
Bons estudos
5(1 - x) - 2x + 1 = - 3(2 + x)
aplica a distributiva
5 - 5x - 2x + 1 = - 6 - 3x
- 7x + 6 = - 6 - 3x
6 + 6 = - 3x + 7x
4x = 12
x = 12 / 4
x = 3
Bons estudos
Chinacoreana:
Aaaaa obrigada vc vai para o céu
respondido por:
0
Olá
5(1 - x) - 2x + 1 = - 3x(2 + x)
5 - 5x - 2x + 1 = - 6 - 3x
- 7x + 3x = - 6 - 6
- 4x = - 12 (-1)
4x = 12
x = 12 / 4
x = 3
5(1 - x) - 2x + 1 = - 3x(2 + x)
5 - 5x - 2x + 1 = - 6 - 3x
- 7x + 3x = - 6 - 6
- 4x = - 12 (-1)
4x = 12
x = 12 / 4
x = 3
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás